PRZESTRZEŃ PRZEDSTAWIONA W POWIEŚCIACH LAURENCE’A STERNE'A W KONTEKŚCIE ROZWOJU GATUNKU POWIEŚCIOWEGO - Umerle, Tomasz (Pracowania Humanistycznych Studiów Interdyscyplinarnych WFPiK UAM, 2011)
Laurence Sterne philosophically relativized the category of space and consistently tried to show epistemological scepticism in his novels. This attitude is different from so called 'classic' novel which emphasizes cultural, social, geographical etc. aspects of space as a fiction's background. Sterne – sometimes even in a discursive way – refused to present these aspects of space and mostly tried to present his narrator's inner space that is being created in the act of narration. To show his sense of relativity and irony, Sterne used some descriptive models, e.g. theatralization. Also, he discussed with typical spatial literary patterns (which he knew for example from adventure novels) by transporting them into his narrative concept of inner space mentioned before. It all indicates that Sterne was aware of the ‘spatial problems’ which novel is said to face in the twentieth century.
Space as presented in the novels by Laurence Sterne in the context of the development of the novel genre
Keywords: Powieść XVIII-wieczna; 18th century novel; Powieść XIX-wieczna; 19th century novel; Sentymentalizm; Sentimentalism; Przestrzeń przedstawiona; Space as presented; Przypadek; Chance